Source and revision in the narratives of David's transfer of the Ark: text, language and story in 2 Samuel 6 and 1 Chronicles 13, 15-16 - Rezetko, Robert C. (The University of Edinburgh, 2005)
The aim of this thesis is to evaluate the relationship between Samuel and Chronicles in a single synoptic story: David's transfer of Israel's sacred ark to Jerusalem in 2 Samuel 6 and I Chronicles 13, 15 -16. Chapter one surveys areas of research related to Samuel and Chronicles. First, the writer summarises research and perspectives on these books and their stories of David's ark transfer. The review highlights competing approaches to Samuel which centre on either sources or composition and on either a diachronic or synchronic methodology. The literary history of Samuel is inadequate in conventional perspective, and must be freshly unfolded, and consequently the relationship of Samuel and Chronicles must also be re- evaluated. Second, the writer reviews the textual evidence for both books, focusing on the received versions, the Greek translations, and in the case of Samuel, on the Dead Sea Scrolls. The witnesses to Chronicles are relatively uniform, and it is suggested that the pluriformity among witnesses to Samuel, and the character of the MT of this book, are related to Samuel's editorial history. In particular, revisers reshaped the story of David's ark transfer in Chronicles and Samuel. Chapter two surveys issues related to synchronic and diachronic approaches to Samuel and Chronicles. The writer suggests that the impasse between these competing approaches may be resolved by the textual- exegetical approach, that is, by using text -critical controls on redactional arguments. The versional evidence substantiates the validity of the diachronic approach -there are earlier and later forms of biblical texts and editions of biblical stories -and scholars can use this evidence to discern literary origins and developments- developments in the versions whose special features, and the reasons for them, may be perceived and appreciated through holistic or final -form readings. Related to this, the writer points out that the issues of text, language (grammar, vocabulary, style) and story are interconnected. Textual variation and grammatical and stylistic incongruities and lexical discrepancies frequently signal editorial developments in biblical compositions. Three helpful models for understanding this developmental process are considered: McKane's rolling corpus, Tov's and Ulrich's literary layers, and Fishbane's inner -biblical exegesis. Finally, it is stated that the principal text -critical aim in this thesis is the detection of earlier and later forms of biblical texts or stories, or to state it differently, the discovery of earlier and later stages in their editorial histories. Using the aforementioned insights and methodologies, chapters three through six closely examine 2 Samuel 6 and the synoptic portions of 1 Chronicles 13, 15 -16. The latter has one short and two lengthy pluses (13.1 -4; 15.1 -24; 16.4- 42) but the text and story in its synoptic material are more primitive than in synoptic MT Samuel. 2 Samuel 6 has one short plus (vv. 20b -23) but the text and story in its synoptic material have developed in MT Samuel beyond LXX Samuel and beyond synoptic Chronicles. In other words, 2 Samuel 6 is a shorter version on the whole, yet in many particulars the MT is a later version of the story of David's ark transfer. The text's 'poor condition' is evidence of its editorial history. Overall, 2 Samuel 6 shows greater textual variation and fluidity, more doublets, and more interpretative difficulties than does 1 Chronicles 13, 15 -16. Specifically, the MT reflects much literary creativity and ideological bias. The readings special to this text relate to an apology of Davidic kingship, an apology of Davidic and Yahwistic character, and cultic practice. In addition, many textual manipulations in MT 2 Samuel 6 connect to the language of stories in 1 Samuel, especially chapters 2, 10- 15, 17 and 25. All these interconnected adjustments point to successive editorial interventions over a substantial period of time and their cumulative appearance and objective may be labelled a literary layer. The thesis concludes with observations regarding the implications of the present investigation for the theories of A. G. Auld.